10.3389/fpsyg.2012.00132 (CrossRef Listing of Deleted DOIs, 2000)
Substance use disorder (SUD) is a psychiatric condition in which recurrent use of psychoactive substances, including alcohol, nicotine, opioids, and stimulants, induces pathological alterations in brain rewards, motivation, and memory circuitry, leading to loss of control over use, compulsive drug-seeking behavior, heightened tolerance, and significant impairment in social functioning. SUD should not be construed as a moral failing or a volitional weakness, but rather as a chronic, relapsing brain disorder. Dependence on tobacco, alcohol, and illicit substances such as opioids and amphetamines constitutes distinct forms of SUD, marked by frequent relapse and associated with profound societal harm and an escalating global public health threat. Although pharmacotherapy and psychosocial interventions remain the mainstay of SUD treatment and can reduce withdrawal symptoms and craving, long-term outcomes are often disappointing. Pharmacotherapy is limited by side effects and high dropout rates, while psychosocial treatments are hampered by poor adherence and uneven access to care-factors that help account for the persistently high relapse rates seen in clinical practice. In contrast, exercise is a safe, non-pharmacological add-on treatment that modulates brain function and alleviates psychiatric and cognitive symptoms associated with addiction. These effects can reduce drug craving, curb compulsive use, and interfere with relapse-promoting processes, offering measurable clinical benefit. In this review, we summarize the effects of exercise interventions on individuals with drug, alcohol, and tobacco addiction. We discuss the potential mechanisms behind these benefits, highlight current limitations in the field, and suggest directions for future research. This review aims to support the development of new intervention strategies and to synthesize the current evidence on the therapeutic effects and mechanistic basis of aerobic exercise in SUD.